1994
DOI: 10.1029/94jc00381
|View full text |Cite
|
Sign up to set email alerts
|

Springtime microwave emissivity changes in the southern Kara Sea

Abstract: Abstract. Springtime microwave brightness temperatures over first-year ice are examined for the southern Kara Sea. Snow emissivity changes are revealed by episodic drops in the 37-to 18-GHz brightness temperature gradient ratio measured by the Nimbus 7 scanning multichannel microwave radiometer. We suggest that the negative gradient ratios in spring 1982 result from increased scatter at 37 GHz due to the formation of a near-surface hoar layer. This interpretation is supported by the results of a surface radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Anderson and Drobot [18] have shown that the MO dates in one region of the Arctic are largely independent of the MO dates in other regions. This is most likely due to the regional nature of cyclonic activity and the associated warm air anomalies [13,19] and increased longwave radiation flux at the surface due to enhanced cloud cover (e.g., [36,37]). Therefore, an extreme MO area accumulation (one that is at either the early or late ends of the 50% MO area range) in a region one year may not appear to be an abnormal year for other regions.…”
Section: Variability In Arctic Ocean Sub-regionsmentioning
confidence: 99%
“…Anderson and Drobot [18] have shown that the MO dates in one region of the Arctic are largely independent of the MO dates in other regions. This is most likely due to the regional nature of cyclonic activity and the associated warm air anomalies [13,19] and increased longwave radiation flux at the surface due to enhanced cloud cover (e.g., [36,37]). Therefore, an extreme MO area accumulation (one that is at either the early or late ends of the 50% MO area range) in a region one year may not appear to be an abnormal year for other regions.…”
Section: Variability In Arctic Ocean Sub-regionsmentioning
confidence: 99%
“…Atmospheric warming above the surface inversion associated with spring cyclones can initiate MO due to enhanced downwelling longwave radiation from thick cloud cover [8]. Further, precipitation and the evolution of the snow grain sizes under freezing surface conditions can impact the Tb signal [9]. The MO date on DOY 68 is unrealistic given the effect of the 20-day window test in this specific event; however given the uncertainties related to the SIC and atmospheric effects for this marginal, first-year ice location, it is also possible that no melting occurred on the later date (DOY 77) when the lower threshold condition was reached.…”
Section: The Barents Seamentioning
confidence: 99%
“…2017, 9,199 18 of 25 including differences greater than 30 days for the Sea of Okhotsk, Baffin Bay, Bering, Greenland, and Barents Seas (Table 3). In most cases, the minima (earlier MO) and maxima (later MO) of the time series are in-phase, although the relative magnitude of the peaks can differ (Figure 7).…”
Section: Original Ahra and Pmwc Trend Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea ice also affects the temperature-albedo feedback (Lutgens and Tarbuck 2001). The albedo varies from 40% to 80% for sea ice, and is about 10% for open water (Crane and Anderson 1994). Also, sea ice emissivity, defined as the ratio of the radiant flux from the material to that of a blackbody at the same physical temperature (Comiso 1983), can give insight into the following factors; ice types, composition, edge, age, thickness, surface characteristics, incidence angle, snow cover, frequency, polarization, ocean currents, weather, and etc.…”
Section: Introductionmentioning
confidence: 99%